A CORPUS-BASED STUDY OF DUAL PRONOUN TRANSLATION - Vaičenonienė, Jurgita (Sustainable Multilingualism / Darnioji daugiakalbystė, 2024)
This article aims to answer the following questions: what is the distribution of dual pronouns in original and translated Lithuanian fiction texts; what English language patterns are rendered by Lithuanian dual pronouns; and how Lithuanian dual pronouns are translated into English. In line with the unique items hypothesis, it is hypothesized that dual pronouns, as a characteristic feature of the Lithuanian language, should be less frequent in translations, as English texts do not have an obvious translation stimulus. Corpus based methods were used for data extraction and analysis. Firstly, from the morphologically annotated ORVELIT corpus, all occurrences of pronouns in original and translated fiction were identified, and all dual forms were extracted. Parallel concordances of dual pronoun translations were obtained from the Lithuanian-English Corpus of Prose LECOP and the Parallel Corpus (English-Lithuanian translation direction) using the ParaConc software (Barlow, 2009). The most frequent forms of personal pronouns were chosen for further analysis: mudu, judu and jiedu. It has been found that differently from initial prediction, Lithuanian translations have similar or slightly higher numbers of dual pronouns in comparison to original Lithuanian texts. The data from English-to-Lithuanian translations shows several patterns rendered by dual pronouns, for example, when English plural personal pronouns describe two referents or when a combination of a personal pronoun and another referent is used with the conjunction and. When translating duals from Lithuanian into English, translators choose English plural forms of pronouns or use the formula ‘pronoun + referent/referent + pronoun’. To compensate for the loss of information about the number of referents or their proximity, translators use the number two. In original English texts, unlike in translated English texts, this usage was not frequent or common.